Realization of Deutsch–Jozsa Algorithm in Rydberg Atoms by Composite Nonadiabatic Holonomic Quantum Computation with Strong Robustness Against Systematic Errors. Issue 11 (17th September 2021) - Liu, Bing‐Bing; Guo, Fu‐Qiang; Yan, Lei‐Lei; Zhang, Shou; Feng, Mang; Su, Shi‐Lei
Abstract: Deutsch–Jozsa (DJ) algorithm, as the first example of quantum algorithm, performs better than any classical algorithm for distinguishing balance and constant functions. Here, a scheme to implement the DJ algorithm in Rydberg atoms using the composite nonadiabatic holonomic quantum computation (NHQC) is presented. Taking advantages of composite loops and holonomic features to resist systematic errors, the scheme of composite NHQC works more robustly compared with the standard dynamic counterparts. By exemplifying the DJ algorithm implementation, the performance of single‐loop NHQC‐, composite NHQC‐, and the dynamic counterpart‐based processes are compared both analytically and numerically, indicating the best robustness of composite scheme to systematic errors. In addition, the combination of composite NHQC and quantum algorithm also provides an alternative pathway for the realization of robust quantum algorithm in the future. Abstract : A scheme to implement the Deutsch–Jozsa algorithm in Rydberg atoms using the composite nonadiabatic holonomic quantum computation (NHQC) is presented, which works more robustly to the systematic errors compared with the schemes of its standard dynamic counterpart and single‐loop NHQC, providing an alternative pathway for the realization of robust quantum algorithm.